Evaluation and heterogeneity of the green total factor productivity of Shandong Province, China: a super-SBM and GML analysis - Minglu Ma; Yifan Yang; Yingying Ma; Zhuangzhuang Wang (Scientific Reports)
Abstract As a pioneering zone for the transformation of old and new growth drivers, the characteristics and issues manifested by Shandong Province during the course of industrial structure adjustment and economic transformation can best represent the green transformation and sustainable development of the Chinese economy. On the basis of multidimensional panel data from 2007 to 2020, this study employs the superefficiency slack-based measure (super-SBM) model, which considers undesirable outputs, and the global Malmquist–Luenberger (GML) index to measure the green total factor productivity (GTFP) of 16 cities in Shandong Province and analyzes the dynamic characteristics of GTFP and its growth drivers from three dimensions—overall characteristics, regional differences, and urban scale levels. The results show that (1) the GTFP of Shandong Province exhibited a year-on-year decline before 2011, transformed into slow growth during 2011–2015, and then presented rapid growth after 2015. Overall, GTFP, technical efficiency, and technological progress increased at average annual rates of 0.95%, 0.74%, and 0.21%, respectively. Before 2015, the variation in GTFP relied mainly on technical efficiency, whereas after 2015, technological progress made a greater contribution to GTFP. (2) The Jiaodong Economic Circle experienced the greatest growth in GTFP, followed by the Provincial Capital Economic Circle, whereas the Lunan Economic Circle exhibited an overall downward trend. The enhancement of technical efficiency was the main driving force for the growth of GTFP in each economic circle and the main cause for the formation of the GTFP gap among economic circles. (3) Compared with other cities, regional megacities such as Jinan and Qingdao possess unparalleled advantages in terms of economy, talent, and infrastructure; therefore, the growth rate of GTFP is significantly greater in these megacities than in other cities.